2004
DOI: 10.1354/vp.41-3-221
|View full text |Cite
|
Sign up to set email alerts
|

A von Willebrand's Factor Genomic Nucleotide Variant and Polymerase Chain Reaction Diagnostic Test Associated with Inheritable Type-2 von Willebrand's Disease in a Line of German Shorthaired Pointer Dogs

Abstract: Heritable, type-2 von Willebrand's disease (vWD) was studied in a line of German Shorthaired Pointers (GSPs) in which some members had a nucleotide variant in exon 28 of the von Willebrand factor (VWF) gene. A polymerase chain reaction (PCR) diagnostic test for the nucleotide variant was developed to establish the disorder's mode of inheritance and to eliminate it from the line. Thirty-six of the 49 GSPs in the line, 14 unrelated GSP controls, and 71 unrelated dogs of various breeds were tested for the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
22
0
4
Order By: Relevance
“…In the present study; vWF: Ag concentration <50% individuals were considered to be vWD positive as reported by Burges et al [2] and Thomas [15] . Von Willebrand's disease is an acquired or inherited bleeding disorder common in humans and dogs [3] . In human beings estimated prevalence of vWD has been reported between 0.01-0.02% [9,16] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study; vWF: Ag concentration <50% individuals were considered to be vWD positive as reported by Burges et al [2] and Thomas [15] . Von Willebrand's disease is an acquired or inherited bleeding disorder common in humans and dogs [3] . In human beings estimated prevalence of vWD has been reported between 0.01-0.02% [9,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Von Willebrand's disease (vWD) is the commonest an acquired or inherited bleeding disorders of dogs and humans being [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations